ANALISIS DAN IMPLEMENTASI SISTEM TRANSAKSI PENJUALAN BARANG DENGAN SMS GATEWAY SEBAGAI PENDUKUNG PROGRAM PELAYANAN PRIMA - Auliya Rahman (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
Applications spare parts sale of goods by sms gateway as a supporting program to the company's excellent service is a system that produces a variety of information that could be useful to support sales activities in one company. Applications spare parts sale of goods was developed to collect, process and store sales data so that data can be traced back to be distributed as a useful information. The realization of the development of this application is the creation of applications that is capable of representing an overall system designed by sms gateway. This application is generated capable of managing sales data, which includes systems approach used in the making of this application using object-oriented methods (object oriented) which emphasizes problem solving software is based on the object. The design of making his application using borland delphi 7 as a program maker and microsoft access 2016 database program and then to display the report using crystal report. The results of this study indicate that the role of computer applications in the information system is very important as a support in improving the quality of sales and service activities in the corporate environment. Keywords: sales application, borland delphi, crystal report, object oriented, sms gateway.